Generation and Validation of miR-100 Hepatocyte-Specific Knock-Out Mice - Yang, Dong; Tang, Sai; Yang, Yan; Yang, Fan; Jiang, Wengang; Liu, Yakun; Zhang, Fengyun; Fang, Haoshu; Wang, Siying; Zhang, Yuxia (Frontiers in Oncology, 2019)
Background: Inactivation of microRNA-100 (miR-100) is involved in hepatocellular carcinoma (HCC) and miR-100 behaves as a tumor suppressor. To understand miR-100 function in HCC genesis and development in vivo, we developed hepatocyte-specific miR-100 deficient mice. Methods: Mice homozygous for floxed miR-100 allele that carried the Alb-Cre transgene (miR-100flox/floxAlb -Cre+) were developed by mating miR-100flox/flox mice with Alb-Cre+/+mice. The mice tails DNA were genotyped using the primers for LoxP sites and Cre recombinase, respectively. The specific deletion of miR-100 in the livers was verified by quantitative Real-time PCR (qRT-PCR). HE-staining was performed for histology analysis. Liver function was assessed by transaminase activity. The metabolic profiles of the hepatocytes were detected using a Seahorse XFe24 extracellular flux analyzer. The direct targets of miR-100 (such as IGF1R-β, mTOR and CDC25A) and HCC related protein (SHP-2) were detected by qRT-PCR and Western blot in liver tissues. Results: The resultant homozygous knockout mice with genotype of miR-100flox/flox-Alb-Cre+ showed an 80% decrease in hepatic miR-100 expression. In adult mice, miR-100 knockout has no effect on the liver function and morphology. In aged mice, HE staining showed that miR-100 knockout caused infiltration of inflammatory cells and expansion of hepatocellular nuclei. Consistently, liver function was impaired in miR-100 knockout aged mice as indicated by increased serum AST and ALT levels. The metabolic analysis demonstrated that the miR-100 knockout hepatocytes tend to adopt glycolysis. The expressions of the miR-100 target genes, such as IGF1R-β, CDC25A and mTOR, were increased. In addition, the known HCC related protein, SHP-2 also was up-regulated in the knockout livers. Conclusions: We successfully generated a miR-100 hepatocyte-specific knock-out mouse model. The malignant transformation related to HCC were observed in aged mice. Therefore, this model is suitable for investigating the mechanism of miR-100 inactivation contributing to HCC genesis in vivo.